Supply bottlenecks - Celasun, Oya,Hansen, Niels-Jakob Harbo,Mineshima, Aiko,Spector, Mariano,Zhou, Jing (International Monetary Fund, 2022)
Supply constraints hurt the economic recovery and boosted inflation in 2021. We find that in the euro area, manufacturing output and GDP would have been about 6 and 2 percent higher, respectively, and half of the rise in manufacturing producer price inflation would not have occurred in the absence of supply bottlenecks. Globally, shutdowns can explain up to 40 percent of the supply shocks. Sectors that are more reliant on differentiated inputs-such as autos-are harder hit. Late last year industry experts expected supply shortages for autos to largely dissipate by mid-2022 and broader bottlenecks by end-2022, but given the Omicron wave, disruptions will last for longer, possibly into 2023. With supply constraints adding to price pressures, the challenge for policymakers is to support recovery without allowing high inflation to become entrenched
10.5089/9798400202476.001
Keywords: Graue Literatur; Output; Supply Constraints; Output; Inflation; Manufacturing and Supply Constraints; PPI Inflation; Prices; Business Fluctuations and Cycles; Producer Price Inflation; Supply-Shock Contribution; Manufacturing; Economic Theory; Industries: Manufacturing; Macroeconomics: Production; Prices; Business Fluctuations; and Cycles: General (includes Measurement and Data); Agriculture: Aggregate Supply and Demand Analysis; Price Level; Inflation; Deflation; Industry Studies: Manufacturing: General; Demand and Supply of Labor: General; Economic & financial crises & disasters; Economics of specific sectors; Economic theory & philosophy; Macroeconomics; Labour; income economics; Supply shocks; Economic theory; Economics: General; Economic sectors; Producer price indexes; Labor shortages; Labor; Currency crises; Informal sector; Economics; Supply and demand; Prices; Manufacturing industries; Price indexes; Labor market